Strengthen Controls and Eliminate the Risks of Infringements of Economic Sanctions - Tudor, Florin (Acta Universitatis Danubius. Œconomica, 2022)
Even if for most of the trade agreements the obligations of the parties are suspended or the termination has already taken place, obviously there are still international contracts in force of some companies with several entities from Russia and Belarus on the list of sanctions introduced by the EU and USA. In practice, there are often those situations that create difficulties in managing contractual obligations as the decisions of European leaders are firm and have largely achieved their objectives. This article will analyze the consequences of terminating/suspending contracts from a legal point of view, the perspective of the economic impact that followed the introduction of economic sanctions, but also how it is necessary to strengthen controls, of any kind, to avoid the risks of violating international sanctions.